Internvention Effort for Individuals with Autism During the COVID-19 Pandemic - Dewi, Karina Wahyu; Purbaningrum, Endang; Budayasa, I Ketut; Andajani, Sri Joeda (Indonesian Journal of Disability Studies, 2022)
Children with autism spectrum disorders need interventions to deal with communication, social interaction, and behavior problems. The Covid-19 pandemic has prevented children with autism spectrum disorders from performing face-to-face interventions outside the home. This study aims to describe the impact of the Covid-19 pandemic on individuals with autism spectrum disorders and to describe the intervention efforts of individuals with spectrum disorders during the Covid-19 outbreak. This study uses a systematic literature review consisting of three main phases, planning the review, conducting the review, and reporting the review, by analyzing 17 articles. The results show that the impact of the Covid-19 pandemic on children with autism is increased stress and anxiety. The cause of this anxiety stress is extreme routine changes that are difficult for children with autism spectrum disorders to experience. Some of the symptoms of behavioral changes as a result of this stress include anxiety, sleep disturbances, irritability, obsessions, impulsivity. Adolescents with autism spectrum disorders are also prone to depression. Therefore, intervention efforts that can be done are through telehealth (online health consultations and interventions), online learning, and family-based interventions with a variety of activities.